1999
DOI: 10.1002/1529-0131(199909)42:9<1917::aid-anr18>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of rheumatoid synovial cell interleukin-12 production by tumor necrosis factor ? and CD40 signals

Abstract: IL-12 production in RA is regulated by 2 different pathways. One pathway is T cell dependent, predominantly through a CD40-CD154 interaction, while the other is T cell independent, mediated through TNFalpha. Inhibition of IL-12 production by interference with CD40-CD154 interaction and TNFalpha production may be a potential therapeutic strategy for treating RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
(41 reference statements)
1
9
0
1
Order By: Relevance
“…Taken together, antigen recognition by CII-specific TCR is necessary for the selective retention of T cells in the inflamed joints, and expression of IL-12 p40 is necessary for the suppression of joint inflammation, and both are required for the local gene therapy. Consistent with this observation are recent reports suggesting that synovial cells from RA patients produce IL-12 and other proinflammatory cytokines in response to CD40 ligation (30). IL-12 has…”
Section: Figuresupporting
confidence: 83%
“…Taken together, antigen recognition by CII-specific TCR is necessary for the selective retention of T cells in the inflamed joints, and expression of IL-12 p40 is necessary for the suppression of joint inflammation, and both are required for the local gene therapy. Consistent with this observation are recent reports suggesting that synovial cells from RA patients produce IL-12 and other proinflammatory cytokines in response to CD40 ligation (30). IL-12 has…”
Section: Figuresupporting
confidence: 83%
“…However, the role of IL-12 seems to be biphasic, as a low dose or early administration promotes the disease, whereas a high dose or administration during the chronic phase can suppress established disease [20,24,25]. In RA, increased levels of IL-12p70 and p40 proteins have been detected in synovial tissue homogenates in comparison with those from patients with osteoarthritis or ankylosing spondylitis [26], and RA synovial cells have been shown to spontaneously produce low levels of p40 and p70 proteins [18,26]. Immunohistochemical and flow cytometric analyses have suggested that CD68 + macrophages are the main source of synovial IL-12 [18,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the regulation of synovial IL-12p70 production has not been adequately studied. Mainly IL-12p40 production has been addressed [26], and therefore the regulation of IL-12p70 production has not been elucidated. Since triggering of CD40 is the main physiological inducer of IL-12 production, and we have earlier shown that synovial fluid (SF) macrophages express increased levels of CD40 [28], we studied the CD154-induced production of IL-12p40 and p70 by SF macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have also demonstrated that CD68ϩ synovial macrophage lineage cells as well as fibroblast-like synoviocytes (FLS) express CD40 (8,9). The ligation of CD40 augments the production of IL-12 in synovial cells and synovial fluid macrophages from RA patients (10,11) and enhances the expression of CD54, CD106, IL-6 (12), stromal cell-derived factor 1 (13), and vascular endothelial cell growth factor (14). In vivo, treatment with a monoclonal antibody (mAb) against CD154 prevents the development of type II collagen-induced arthritis in mice (15).…”
mentioning
confidence: 99%